Spatial Distribution of the Local Meteorological Fields and Dust Concentration in Kakheti Atmosphere in Case of the Northern Background Wind - Gigauri, Natia G.; Surmava, Aleksandre A. (Journals of Georgian Geophysical Society, 2018)
Spatial distribution of meteorological fields and dust concentrations in case of northern background winds is studied by means of the model of mesoscale atmospheric processes evolution at the territory of Kakheti and numerical integration of transfer-diffusion of passive admixtures. It is shown that the Kakheti terrain has significant impact on formation of meteorological fields in boundary layer. The impact of terrain is substantially weaker in free atmosphere. Influence of regional terrain on background flow causes formation of horizontal and vertical swirls and waves directed along the background flow. There is a wave not only in atmospheric boundary layer, but also in free atmosphere. Vertical vortexes are formed on windward and leeward sides of the Greater and Lesser Caucasus Mountains, some of them are in the vicinity of ranges. Sizes of formed vortexes are depended on ridge width and height or on gorge depth. Pictures of dust spatial distribution are obtained. Dust dispersion areas in cities are determined. Dust dispersion kinematics is studied. It is obtained, that in 2-100 m atmospheric layer dust dispersion mainly occurs through turbulent diffusion. In layer from 100 meters to 1 km height the processes of diffusive and advective transfer are equal, while above 1 km advective transfer of dust is primary.